Characterisation of a novel microtubule inhibitor and its therapeutic potential - Dave, Nikita (2024)
The dynamic instability of microtubules allows them to perform a diverse range of functions, including spindle formation and chromosome segregation during mitosis. Uncontrolled cell division is a hallmark of cancer, and drugs that inhibit microtubule dynamics to supress cell division are routinely used in chemotherapy. EFA6 and MCAK are microtubule destabilisers with differing modes of function, with the same result of an inhibition of microtubule dynamics. EFA6, a negative regulator of axonal growth, inhibits microtubule polymerisation through an 18-residue motif known as the microtubule elimination domain, or MTED. Apart from its microtubule inhibition abilities, little is known about the binding properties of this peptide. Here, I show that MTED has a strong affinity for the α/β-tubulin subunit, <10nM, and inhibits its polymerisation by directly binding to this subunit and sequestering it. Further investigations using an MTED-GFP DNA construct show that this peptide inhibits cell proliferation as a direct result of its microtubule inhibition activities, warranting attempts to recreate this result by externally adding synthetic peptide, an area still under investigation. Finally, I use a synthetic version of the kinesin-13 motor domain, Anc13, and study its depolymerisation abilities when placed in the context of the full length MCAK protein. This construct depolymerises microtubules nine-fold faster than wtMCAK, and promotes internal breakage of microtubules, suggesting that the ancestor of this family was a “super-depolymerase”. It is likely that the Kinesin-13 family, over time, moved away from this hyperactive depolymerisation activity to a slower, but much more controlled motor domain. By studying two microtubule destabilising proteins with differing modes of function, I aim to increase our understanding of microtubule targeting agents and aid in the development of novel therapeutics to combat the challenges posed by acquired drug resistance and lack of drug specificity.